2018
DOI: 10.1002/nau.23339
|View full text |Cite
|
Sign up to set email alerts
|

A real‐world experience with augmentation enterocystoplasty—High patient satisfaction with high complication rates

Abstract: AE is a procedure with long-term durability and high rates of patient satisfaction. However, several bothersome complications affecting life quality may occur. Both patients and doctors thus need to consider possible outcomes carefully before the operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 23 publications
2
16
0
Order By: Relevance
“…The median age at the moment of surgery was 15 years (5-39). The median follow-up was 20 years (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). No patient was lost to follow-up.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The median age at the moment of surgery was 15 years (5-39). The median follow-up was 20 years (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). No patient was lost to follow-up.…”
Section: Resultsmentioning
confidence: 99%
“…One study showed recurrent bacteriuria rate of 75%, but only a 20% incidence of troublesome UTI, 13 while another article reported 42% of UTI. 15 Antibiotic prophylaxis causes multi-resistant bacteria and there is no evidence that it reduces UTI episodes. 23 Research is needed to determine the best practice for dealing with UTIs.…”
Section: Resultsmentioning
confidence: 99%
“…However, although some patients were able to void spontaneously with the Crede maneuver, 76% of the patients were completely dependent on CIC. Thus, patients might ultimately opt for an indwelling urethral catheter or cystostomy for convenience of bladder emptying [97].…”
Section: Quality Of Life Comparison Between Repeated Detrusor Botulinum Toxin a Injections And Augmentation Enterocystoplasty In Patientsmentioning
confidence: 99%
“…(F) Affected urethral wall with stricture lesion can be replaced by an electrospun scaffold through onlay or inlay fashion. Veeratterapillay et al, 2013;Wu and Kuo, 2018). Therefore, clinicians and basic scientists have investigated alternate therapeutic methods through the recruitment of modern technologies.…”
Section: Bladder Tissue Engineeringmentioning
confidence: 99%